Properties enhancement of Al-Zn-Mg alloy by retrogression and re-aging heat treatment - Zaid H.R.; Hatab A.M.; Ibrahim A.M.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The higher strength 7xxx aluminum alloys exhibited low resistance to stress corrosion cracking (SCC) when aged to the peak hardness (T6 temper). The overaged alloys (T7 temper) developed to enhance the SCC with loss in the strength of the alloy. Recently, retrogression and re-aging (RRA) heat treatments are used for improving the SCC behavior for alloys in T6 tempers such as 7075, 7475 and 8090. In this study, an application of retrogression and re-aging heat treatment processes are carried out to enhance toughness properties of the 7079-T651 aluminum alloy, while maintaining the higher strength of T651-temper. The results of charpy impact energy and electrical conductivity tests show a significantly increases in absorbed energy and electrical conductivity values, when the alloys are exposed to various retrogression temperatures (190, 200, 210°C) and times (20, 40, 60 minutes), and then re-aged at 160°C for 18 hours.